LiBH4 nanoconfined in activated carbon nanofiber for reversible hydrogen storage. (22nd March 2015) - Thiangviriya, Sophida; Utke, Rapee
Abstract: New host material of activated carbon nanofiber (ACNF) prepared from carbonization and KOH activation of polyacrylonitrile (PAN)−based fibers is proposed for nanocofinement of LiBH4 . Nanocofinement and homogeneous distribution of LiBH4 in ACNF are confirmed. Remarkable reduction of onset and main dehydrogenation temperatures of LiBH4 (Δ T  = 128 and 118 °C, respectively) is obtained together with suppression of B2 H6 release during dehydrogenation. Inferior hydrogen content released during cycling from nanoconfined LiBH4 in ACNF at 350 °C under vacuum is due to partially unconfined LiBH4 and formation of stable Li2 B12 H12 phase. However, nanoconfined LiBH4 in ACNF desorbs and preserves (after three release and uptake cycles) up to 11.7 and 10.1 wt.% H2 with respect to LiBH4 content, respectively. Also, LiBH4 can be rehydrogenated at significantly milder condition after nanoconfinement in ACNF, that is, Δ T  = 250 °C and Δ p (H2 ) = 270 bar with respect to bulk LiBH4 . It could be claimed that not only positive influence of nanoconfinement as well known and frequently reported, but also catalytic effect and good thermal conductivity of ACNF itself can probably synergistically favors hydrogen sorption kinetics of LiBH4 . Highlights: New host material for nanoconfinement of LiBH4 . Lower onset dehydrogenation temperature than bulk LiBH4 (Δ T  = 128 °C). Milder rehydrogenation condition than bulk LiBH4 (Δ T  = 250 °C, Δ p (H2 ) = 270 bar). Suppression of B2 H6 release during dehydrogenation. High H2 content released and reproduced at moderate condition.